Intersecting Dynamics: The Influence of Macroeconomic Factors and Financial Development on Interest Rate Spreads in Uganda - Musiita, Benjamin; Kijjambu, Frederick Nsambu (Journal of Economics and Behavioral Studies, 2024)
The study investigates the factors influencing interest rate spreads in Uganda’s banking sector, focusing on inflation, GDP, Real Effective Exchange Rate (REER), private sector credit, and financial development. Using an Autoregressive Distributed Lag (ARDL) model on data from 2001 to 2022, it examines short and long-term dynamics between these variables and interest rate spreads, within the liquidity preference theory framework. In the short run, inflation and GDP have marginally significant positive impacts on interest rate spreads, indicating that initial increases may widen spreads due to heightened liquidity demand and economic activity. Conversely, in the long run, these factors exhibit significant negative effects, suggesting a stabilizing influence of monetary policy and increased market efficiency. The REER’s short-term impact reflects currency value fluctuations affecting risk premium adjustments, which diminish in the long run as markets adapt. The study also explores the interaction between inflation and financial development, represented by private sector credit, on interest rate spreads. Short-term results show a non-significant negative moderation by financial development, while long-term analysis suggests a potential amplification of inflation’s effects as the financial sector matures, requiring nuanced financial development policies. Policy recommendations stress the importance of stabilizing inflation and exchange rates to control interest rate spreads in the short term. Long-term strategies include enhancing banking sector efficiency and promoting competitive practices to mitigate the negative effects of economic growth on interest rate spreads.